A remarkable new genus of Thripinae (Thysanoptera, Thripidae) with enlarged metathoracic furca, from Southeast Asia - Masumoto, Masami; Okajima, Shûji (Zootaxa, 2005)
Trachynotothrips striatus gen. et sp. n. and T. brevispinis gen. et sp. n. are described from South Vietnam and Thailand, respectively, each with an enlarged metathoracic furca. Despite this furca, this new genus is closely related to Trichromothrips Priesner in the Thripinae in its chaetotaxy, rather than to the Dendrothripinae.